Sustainability and sustainable projects: Bibliometric study - Manzano - Durán, Omaira; Peñaranda - Peñaranda, Marta Milena; Luna - Quintero, Juan Carlos (Universidad Francisco de Paula Santander, 2021)
The present research responds to a descriptive longitudinal quantitative approach in order to construct a bibliometric analysis on the sustainability of the projects, evidencing the state of science in this important area. Through the use of the Scopus database, Excel and the VOSviewer software, indicators of the 550 documents found from 1990 to 2020 were analyzed. As a result, it was found that the quality and quantity of the documents as well as their structure is high. However, there is a need to improve book publications in this area. From the map of co-occurrence carried out, it is possible to identify 3 clusters or categories analyzed: Sustainability, sustainable development and sustainable projects.